RELIGIOUS DIGITAL LITERACY OF URBAN MUSLIM SOCIETY IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Sukijan Athoillah; Muhammad Khakim Ashari; Muhammad Badat Alauddin (Akademika : Jurnal Pemikiran Islam, 2023)
The current era of disruption is marked with the rapid flow of information on the internet, including religious content. The emergence of the internet clearly has a positive influence although there is also a negative impact. This article aims to determine the use of information and communication technology products in the context of religious literacy and religious digital literacy in urban communities in Indonesia. This research is a library research with a systematic literature review (SLR) approach. Sources of data in this study came from books and journal articles with a reputation in accordance with the theme or content of the discussion, totaling 58 references and published in the last 5 years. The analysis technique uses content analysis. The findings from the results of this study are that information and communication technology products have been widely used in many sectors of human life, including religion. Users who have gadgets or laptops (PCs) make it a tool for accessing religious content with the help of the internet. This is influenced by the dependence on the internet and a variety of religious content that is increasingly massively spread in cyberspace, especially for urban Muslim communities. Religious digital literacy can be used as a real solution to educate the public about access to digital information. This digital literacy can be used as a provision and foundation for someone to face the current digital era, so that they are not only able to access and find information. But more than that, it is hoped that information can also be validated by referring to the source of origin.